Total obstruction of small intestine due to metastatic lung adenocarcinoma - Widyanti, Ni Nyoman Ayu; Putra, Wayan Wahyu Semara; Yaniswari, Ni Made Dwita; Novitasari, .; Suhardinatha P., Kadek Agus (International Journal of Research in Medical Sciences, 2023)
Lung cancer with symptomatic small intestinal metastasis is a rare case but potentially fatal with poor diagnosis in most advanced stages. A-82 years old male patient with chronic cough, chest pain, progressive dyspnea abdominal pain, obstipation, and distended abdomen. Chest computed tomography (CT)-scan revealed right inferior pulmonary lobe of lung tumor. Abdominal X-ray and abdominal ultrasound showed ileus obstruction features. The patient underwent emergency laparotomy under the diagnosis of total ileus obstruction. Surgical resection of two masses in the small intestinal were performed with ileo-ileal anastomosis. Histomorphology of the surgical specimen revealed poorly differentiated adenocarcinoma involving the small intestine without precursor lesions that suggested a metastasis. The patient underwent thoracentesis and pleural fluid cytology that reported seeding of non-small cell lung cancer (NSCLC) tend to adenocarcinoma type. A diagnosis of lung adenocarcinoma with small intestinal metastasis was concluded based on correlation of these anatomopathological examination. Clinicians should consider possibility of lung cancer with small intestinal metastasis in patient with abdominal symptoms.